Description of the larva and biological notes on Vermiophis taihangensis Yang & Chen, 1993 (Diptera: Vermileonidae) from China - Ovtshinnikova, O. G.; Wang, Zhiliang; Ovchinnikov, A. N.; Wang, Xinli; Krivokhatsky, V. A. (Zootaxa, 2014)
Unmixed colonies of larval antlions and wormlions in similar pits were found in the Xiaolongmen National Forest Park in the Taihang Shan, China. A male of Vermiophis taihangensis Yang & Chen, 1993 was reared from a larva and a morphological description of the third instar larval wormlion is presented. The larva of Vermiophis taihangensis differs from the related species V. ganquanensis Yang, 1979 in the well developed sclerotized stigmata on abdominal segment 4, but is similar in the structure of the lateral row of setae and the same number of spines (6) on the pseudopod on the abdominal segment 1.